Economic innovations : creating new instruments to improve economic life - Webster, Beth; Scales, Bill (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Economic system innovations have had a profound impact on our lives, from the invention of banking in the middle ages to the United Nations institutions post-WWII. However, their intangible nature means that few people identify these changes alongside physical inventions. This book is a series of vignettes about changes to Australian institutions and systems that have significantly improved economic and social well-being. Although invention is normally an incremental process, with copying and adaption being the norm, the authors focus on reforms that were principally new to the world at the time of implementation. The book is not about the reforms and how well they worked, per se, rather about the people and the political struggle to get them adopted. The authors have chosen to focus on the stories where Australia has either taken a global leadership role or made a considerable advance in a particular new institution. What these stories show is that leadership in institutional innovation can come from many quarters: academia, the community, politics and the bureaucracy. Often the most successful teams combine people from all quarters albeit with support from the fourth estate. The work shows how many reforms began with modest beginnings, often an ordinary person with a vision, and how often it takes several attempts to get change accepted. This key volume can be used to teach students of economics, political economy and politics. It illustrates the type of networks, actions and advocacy that is needed to get reform implemented and is written in a style to also engage policy and think-tank audiences. Beth Webster is the Director of the Centre for Transformative Innovation at Swinburne University of Technology and Pro Vice Chancellor. She has a long abiding interest in economic research and the political economy of policy and has worked for several government departments and three public research institutes at Monash, Melbourne and Swinburne Universities. Bill Scales has held governance, advisory and executive positions in business, industry, government and the not-for-profit sectors. These include manufacturing, telecommunications, the government sector, aged care, economic infrastructure and education sectors. He has been Chair or Panel Member on 13 major national and Australian state government inquiries and reviews across the economy"--
OCLC-licensed vendor bibliographic record.
Keywords: Economics -- Australia; Australia -- Economic conditions; BUSINESS & ECONOMICS -- Economics -- General